MAPPING CURRENT TRENDS OF EFL TEACHING AND LEARNING RESEARCH PRACTICES IN INDONESIA - Mali, Yustinus Calvin Gai; Timotius, Anne Indrayanti (International Journal of Education, 2023)
To date, there have been very few studies that map the major research trends in English as a Foreign Language (EFL) contexts, such as those in Indonesia. To address that gap and to benefit undergraduate and graduate students, EFL researchers, or practitioners looking for a current research topic and theories to frame their studies, this paper reviews the past research studies (n=53) published in four Indonesian national journals to explore Indonesia’s EFL research trends in 2020, including research topics, theoretical frameworks, and research methods. The journals were selected because of their focus and scope related to English language teaching and education as well as their rank in Sinta 1 and Sinta 2 (two of the highest levels out of six Sinta levels) of the Indonesian web-based research information system. Based on a holistic review of the articles checked by the peer-debriefing strategy to ensure the review’s credibility, the analysis results show that the previous studies mainly explore English teaching strategy and education technology research areas and use fairly old theories as their theoretical framework. As for the research method, most of the studies use a qualitative research method, take place in university settings, and involve university students as their research subjects. The meanings of the analysis results, teaching implications for a research class, and directions for further research are presented.